(untitled) - Annie Gendron; Michel Landry; Chantal Plourde; Natacha Brunelle (Criminologie, 2009)
Results from a study on the use of psychoactive substances in Nunavik are presented. The qualitative part of the study consisted of 108 semi-structured qualitative interviews with youth, parents, leaders and elders of four villages. Thematic content analysis of the material revealed different reasons and consequences of substance use and abuse in Nunavik, from the respondent’s standpoint. Among the reasons, respondents evoked pleasure, boredom and lack of activities, “colonization,” coping about different problems (poverty, victimization and suicide) and also intergenerational transmission. Concerning consequences, they mostly talked about family impacts including intimate violence and child neglect, but also about other deviant behaviors like drinking and driving and lucrative crimes. These results are discussed according to actual knowledge about causes and consequences of substance use among Inuit and non-Inuit. Dans le présent article sont exposés les résultats d’une étude sur la consommation de substances psychoactives au Nunavik. Le volet qualitatif de cette étude comporte 108 entretiens semi-dirigés auprès de jeunes, de parents, de leaders et d’Aînés de quatre villages. L’analyse de contenu thématique des résultats a mis en lumière différentes raisons et différents effets de la consommation au Nunavik du point de vue des participants. Parmi les raisons évoquées par les interviewés, on retrouve le plaisir, l’ennui et le manque d’activités, la « colonisation », l’adaptation (coping) à divers problèmes (pauvreté, abus, suicide) et la transmission intergénérationnelle. Sur la question des conséquences de la consommation, les effets sur la famille, dont la violence conjugale et la négligence envers les enfants, mais aussi les comportements déviants, incluant la conduite avec capacités affaiblies, les voies de fait et les délits lucratifs ont été évoqués. Ces résultats sont discutés à la lumière des connaissances actuelles sur les causes et conséquences de la consommation chez les Inuits et les non-Inuits. ...